Ovarian development of female mud crab, Scylla serrata supplemented with cholesterol and injected with serotonin - Pattiasina, Betsy J.; Junior, M. Zairin; Mokoginta, I.; Affandi, R.; Manalu, W. (Jurnal Akuakultur Indonesia, 2010)
Cholesterol is known to play an important role in nutrition of crustacean and function as a precursor for steroids synthesis, while neurohormone of serotonin could induce ovarian maturation in crustacean. Ovarian development of adult females Scylla serrata was induced by adding cholesterol in the diet and serotonin injection. This research was designed to study the effectiveness of cholesterol supplementation and serotonin injection in ovarian development. Broodstocks were stocked in nine experimental units in three fiber tanks. The fiber tank was equipped with sands substrate and flow through seawater system. The experimental crabs were assigned into a completely randomized design with a 3 x 3 factorial arrangement. The first factor was cholesterol supplementation in the diet with 3 levels (0, 0,5 and 1,0%). The second factor was serotonin injection with 3 levels (0, 5 and 10 μg/g BW). Samples of broodstock were taken every four days to evaluate the stages of ovarian maturity and parameters were used to evaluate the ovarian maturation stage are gonad index (GI) and oocyte diameter, concentration of estradiol 17β, yolk protein concentrations, and fecundity. Results showed that female crabs supplemented with 0,5% cholesterol and a combination of cholesterol 0,5% supplementation and injection serotonin with a dose of 10 μg/g BW had better reproduction development. It is concluded that ovarian development of Scylla serrata could be improved by cholesterol supplementation and serotonin injection. Key words: Cholesterol, serotonin, ovarian development, Scylla serrata   ABSTRAK Kolesterol diketahui merupakan nutrien spesifik yang berperan dalam sisntesis hormon steroid dan mengontrol reproduksi, sementara serotonin merupakan salah satu neurohormon yang dilaporkan dapat merangsang pematangan ovari dan pemijahan pada krustase. Penelitian ini bertujuan untuk mengetahui pengaruh tingkat pemberian kolesterol yang optimal dalam pakan buatan, serta dosis penyuntikan serotonin yang efektif untuk mempercepat proses perkembangan dan pematangan ovarium induk kepiting bakau Scylla serrata. Pemeliharaan induk dilakukan dengan menggunakan tiga buah bak fiber. Bak pemeliharaan dilengkapi dengan substrat pasir dan sistim air laut mengalir. Eksperimen menggunakan rancangan acak lengkap (RAL) pola faktorial, dengan 9 satuan percobaan. Faktor pertama, suplemen kolesterol didalam pakan dengan 3 tingkat dosis (0; 0,5; dan 1%) dan faktor kedua, injeksi serotonin dengan 3 tingkat dosis (0, 5, dan 10 μg/g bobot tubuh). Pengamatan terhadap tingkat kematangan ovari dilakukan setiap 4 hari sekali. Paramater pengambilan sampel meliputi  tingkat kematangan ovari, indeks gonad dan diameter oosit, konsentrasi estradiol 17β, konsentrasi protein yolk, dan fekunditas. Hasil penelitian menunjukkan bahwa induk kepiting yang disuplementasi dengan dosis kolesterol 0,5% dan induk kepiting yang mendapat perlakuan kombinasi, suplementasi kolesterol 0,5% dan injeksi serotonin dosis 10 μg/g bobot tubuh dapat menghasilkan perkembangan ovari yang terbaik. Jadi kolesterol dan serotonin dapat digunakan untuk meningkatkan perkembangan ovari. Kata-kata kunci: Kolesterol, serotonin, perkembangan ovari, Scylla serrata